EFFECTIVENESS OF USING TEXT EDITORS IN THE PERSONAL WEB DEVELOPMENT PROCESS BY BEGINNING LEVEL STUDENTS - Muhammad Syarani, Machrizzandi (Jurnal INSYPRO (Information System and Processing), 2025)
This study aims to evaluate the effectiveness of using the Visual Studio Code (VSCode) text editor in the development process of personal websites by novice-level university students. As the demand for web programming skills continues to grow in the digital era, the choice of development tools plays a crucial role in determining student success and productivity. The research employed a qualitative observational approach with a descriptive method. The findings indicate that all participants successfully completed their personal website projects within a relatively efficient time frame, averaging between 8 and 12 hours. VSCode's built-in features significantly facilitated the coding process, particularly through automated linting and IntelliSense, which helped reduce HTML and CSS syntax errors. The use of extensions such as Live Server and Prettier further enhanced testing efficiency and code readability. In terms of output quality, all websites met basic standards for functionality and navigational structure, with visual variations reflecting each student’s creativity.